Crystal structures and conformations of two Diels–Alder adduct derivatives: 1, 8-bis(thiophen-2-yl)-14-oxatetracyclo[6.5.1.02, 7.09, 13]tetradeca-2(7), 3, 5-trien-10-one and 1, 8-diphenyl-14-oxatetracyclo[6.5.1.02, 7.09, 13] tetradeca-2, 4, 6-trien-10-one. (February 2015) - Gopinath, S.; Narayanan, P.; Sethusankar, K.; Nandakumar, Meganathan; Mohanakrishnan, Arasambattu K.
No abstract available